A gaped reflective film and a photovoltaic module

CN224863322UActive Publication Date: 2026-10-16HANGZHOU FUMO NEW MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202522419189.4
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2025-11-14
Publication Date
2026-10-16
Estimated Expiration
2035-11-14

AI Technical Summary

Technical Problem

然而,这种方案必须配合金属镀层;金属加工过程产生重度污染,而且金属镀层的导电特性容易引起汇流条和焊带发生短路,干扰电池片正常工作

Benefits of technology

[0018]This invention provides a gap reflective film and a photovoltaic module. The gap reflective film includes a film layer and a reflective film layer stacked sequentially. The reflective film layer includes a connecting layer, an intermediate reflective layer, and a prism reflective layer stacked sequentially. The reflective film layer is bonded to the film layer by the connecting layer. The prism reflective layer has multiple inclined surfaces forming convex prisms. The gap reflective film on the cell gaps, cell perimeters, and solder strips can change the light propagation path through the prism structure of the reflective film layer, reflecting the light that originally passed through the cell gaps to the inside of the front glass, and then reflecting it back to the cell surface, thereby improving the utilization rate of sunlight. Furthermore, the gap reflective film provided by this invention is made of non-metallic material, requiring no aluminum plating, making it environmentally friendly and avoiding metal pollution. Using the gap reflective film does not affect the power generation function of the cells. Simultaneously, the interlayer structure design reduces processing temperature requirements, improving production efficiency and product reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN224863322U_ABST
    Figure CN224863322U_ABST
Patent Text Reader

Abstract

The utility model provides a kind of gap reflective film and a kind of photovoltaic module, the gap reflective film includes glue film layer and reflective film layer that are sequentially superposed, the reflective film layer includes sequentially superposed connection layer, intermediate reflective layer and prism reflective layer, the reflective film layer is bonded to glue film layer by connection layer, the prism reflective layer is formed by multiple inclined faces to form convex prism upwards.Gap reflective film installed on cell gap, cell periphery and solder strip can change the propagation path of light by the prism structure of reflective film layer, reflect the light originally through the cell gap to the inside of front plate glass, then reflect back to the surface of cell sheet again through the inside of front plate glass, thereby improve solar utilization, improve the power generation of photovoltaic module under the premise of not need to be plated with aluminium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This utility model relates to the field of photovoltaic cell technology, and in particular to a gap reflective film and a photovoltaic module. Background Technology

[0002] In solar cell applications, light conversion efficiency directly affects power generation. In existing technologies, sunlight directly hitting the solar cells can be effectively absorbed and utilized, but sunlight hitting the gaps between the cells passes through the solar module, resulting in energy waste. To improve light energy utilization, the industry typically uses reflective films placed between the cells, around the cells, or on the solder strips to reflect the transmitted sunlight back to the cells, allowing it to be reabsorbed and converted into electrical energy.

[0003] Traditional reflective films primarily employ two technical approaches: the first involves adding reflective materials to a PET substrate to form a reflective layer. While this increases light reflectivity, it fails to change the reflection direction, resulting in ineffective absorption of reflected light by the solar cell. Due to the unique properties of PET, directly fabricating a prism structure on its surface requires extremely high reaction temperatures, which are incompatible with the temperatures of subsequent manufacturing processes, increasing production costs and impacting efficiency. Based on this, those skilled in the art have identified a second approach: setting a resin prism structure on the PET substrate surface and then plating it with aluminum. This alters the reflection direction through the resin prism structure, while the aluminum layer achieves high reflectivity. However, this approach requires a metal plating layer; the metal processing generates significant pollution, and the conductive properties of the metal plating layer can easily cause short circuits in the busbars and solder strips, interfering with the normal operation of the solar cell.

[0004] To address the aforementioned issues, there is an urgent need for a gap reflective film that can achieve high reflectivity and precisely change the reflection direction; at the same time, it should be made of environmentally friendly materials, effectively improve the power generation of solar cells without affecting their power generation function, and balance optical performance and environmental protection requirements without the need for aluminum plating. Utility Model Content

[0005] This utility model provides a gap reflective film and a photovoltaic module, which have the advantages of improving the utilization rate of sunlight and using environmentally friendly materials without the need for aluminum plating. This utility model provides the following technical solution:

[0006] This utility model first provides a gap reflective film, which includes an adhesive film layer and a reflective film layer stacked in sequence. The reflective film layer includes a connecting layer, an intermediate reflective layer and a prism reflective layer stacked in sequence. The reflective film layer is bonded to the adhesive film layer through the connecting layer. The prism reflective layer is formed by multiple inclined surfaces forming a convex prism.

[0007] Furthermore, the height of the convex prism is 10–25 μm.

[0008] As a preferred embodiment of this utility model, the thickness ratio of the prism reflective layer, the intermediate reflective layer and the connecting layer is 1:(1~3):(0.5~2).

[0009] As a preferred technical solution of this utility model, the prism reflective layer and the intermediate reflective layer are composed of a base material, inorganic fillers and UV additives, wherein the base material forms a continuous phase and the inorganic fillers, base material and UV additives are fully mixed.

[0010] In a preferred embodiment of this invention, the base material is polypropylene (PP); the inorganic filler is titanium dioxide.

[0011] In a preferred embodiment of this invention, the connecting layer is a blend of polypropylene base material and adhesive resin.

[0012] As a preferred embodiment of this utility model, the adhesive film layer is selected from functional grafts of ethylene copolymers such as ethylene-vinyl acetate copolymer (EVA), ethylene-methyl acrylate copolymer (EMA), ethylene-ethyl acrylate copolymer (EEA), ethylene-butyl acrylate copolymer (EBA), ethylene-methyl methacrylate copolymer (EMMA), ethylene-acrylic acid copolymer (EAA), and ethylene-α-olefin copolymer (POE).

[0013] As a preferred technical solution of this utility model, the base material, inorganic filler and UV additive of the prism reflective layer are mixed in a mass ratio of (60-75):(20-35):(0.1-5).

[0014] As a preferred technical solution of this utility model, the base material, inorganic filler and UV additive of the intermediate reflective layer are mixed in a mass ratio of (45-65):(30-50):(0.1-5).

[0015] As a preferred embodiment of this invention, the thickness of the adhesive film layer is 30–60 μm; the thickness of the reflective film layer is 80–150 μm.

[0016] This utility model also provides a photovoltaic module, wherein any of the above-mentioned gap reflective films are provided in the gaps, peripheries or solder strips of the battery cells, and the gap reflective film is bonded to the inner surface of the glass back panel of the battery module through an adhesive film layer.

[0017] Compared with the prior art, the beneficial effects of this utility model are as follows:

[0018] This invention provides a gap reflective film and a photovoltaic module. The gap reflective film includes a film layer and a reflective film layer stacked sequentially. The reflective film layer includes a connecting layer, an intermediate reflective layer, and a prism reflective layer stacked sequentially. The reflective film layer is bonded to the film layer by the connecting layer. The prism reflective layer has multiple inclined surfaces forming convex prisms. The gap reflective film on the cell gaps, cell perimeters, and solder strips can change the light propagation path through the prism structure of the reflective film layer, reflecting the light that originally passed through the cell gaps to the inside of the front glass, and then reflecting it back to the cell surface, thereby improving the utilization rate of sunlight. Furthermore, the gap reflective film provided by this invention is made of non-metallic material, requiring no aluminum plating, making it environmentally friendly and avoiding metal pollution. Using the gap reflective film does not affect the power generation function of the cells. Simultaneously, the interlayer structure design reduces processing temperature requirements, improving production efficiency and product reliability. Attached Figure Description

[0019] The accompanying drawings are provided to further illustrate the present invention and form part of the specification. They are used together with the embodiments of the present invention to explain the present invention, but do not constitute a limitation thereof. In the drawings:

[0020] Figure 1 This is a schematic diagram of the structure of the gap reflective film of this utility model;

[0021] Figure 2 This is a schematic diagram of the reflective film layer of this utility model;

[0022] Figure 3 This is a schematic diagram of the structure of the photovoltaic module of this utility model;

[0023] In the diagram: 1. Gap reflective film; 2. Reflective film layer; 3. Connecting layer; 4. Adhesive film layer; 5. Prism reflective layer; 6. Intermediate reflective layer. Detailed Implementation

[0024] The technical solutions of the present utility model will be clearly and completely described below with reference to the accompanying drawings of the embodiments. Obviously, the described embodiments are only some embodiments of the present utility model, and not all embodiments. Based on the embodiments of the present utility model, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present utility model.

[0025] In a typical embodiment of this application, a gap reflective film 1 is provided, such as Figure 1-2As shown, the gap reflective film 1 includes a film layer 4 and a reflective film layer 2 stacked sequentially. The reflective film layer 2 includes a connecting layer 3, an intermediate reflective layer 6, and a prism reflective layer 5 stacked sequentially. The reflective film layer 2 is bonded to the film layer 4 through the connecting layer 3. The prism reflective layer 5 has multiple inclined surfaces forming a convex prism to change the light propagation path. The height of the convex prism is 10-25 μm. It should be noted that the prism height refers to the vertical distance of a single prism unit. The apex angle of the convex prism can be designed according to the geographical location and lighting conditions of the application site, so that the gap reflective film provided in this application can cover light with different incident angles. Specifically, when used in different latitude regions of China, as the installation angle of the photovoltaic module changes, the apex angle of the convex prism is generally designed to be 115°-125°, preferably 120°.

[0026] It should be noted that the connecting layer 3 is used to bond the reflective film layer 2 and the adhesive film layer 4, which effectively solves the problem of interfacial bonding between heterogeneous material layers and ensures that the gap reflective film 1 maintains a stable interlayer structure during the long-term operation of the photovoltaic module.

[0027] In some embodiments of this application, the film layer 4 is selected from functional grafts of ethylene copolymers such as ethylene-vinyl acetate copolymer (EVA), ethylene-methyl acrylate copolymer (EMA), ethylene-ethyl acrylate copolymer (EEA), ethylene-butyl acrylate copolymer (EBA), ethylene-methyl methacrylate copolymer (EMMA), ethylene-acrylic acid copolymer (EAA), and ethylene-α-olefin copolymer (POE).

[0028] In some embodiments of this application, the thickness of the adhesive film layer 4 is 30-60 μm, and the thickness of the reflective film layer 2 is 80-150 μm.

[0029] Specifically, the reflective film layer 2 is a composite layer with light reflection function and surface micro / nano structures. Its surface convex prism structure is formed through surface micro / nano structure processing, used to directionally reflect incident light to the surface of the solar cell. The convex prism refers to a geometric structure composed of inclined surfaces, which can be formed on the surface of the reflective film layer 2 through surface micro / nano structure processing technology. The light refraction path is controlled by adjusting the tilt angle. In essence, the reflective film layer 2 has the dual function of light reflection and changing the direction of light reflection. When light shines on the prism surface, the inclined surfaces cause the incident light to refract and reflect, and its propagation path is ultimately adjusted towards the solar cell after secondary reflection. The connecting layer 3 is used to enhance the interlayer bonding strength, achieving low-temperature bonding through the use of chemically compatible materials. The adhesive film layer 4 is directly bonded to the gaps, edges, or solder strips of the solar cell, forming a stable bonding interface through a hot-melt process to complete the final assembly.

[0030] Compared with existing technologies, the reflective film layer 2 of the gap reflective film 1 enables directional light control, the connecting layer 3 ensures the reliability of interlayer bonding, and the adhesive film layer 4 completes the final assembly. The synergistic function of each layer enables active control of the light propagation path, allowing light not absorbed by the solar cell to be directionally reflected to the effective area, significantly improving the utilization rate of sunlight. Together, they form a light reflection system that does not require metal coating, eliminating the risks of metal conductive interference and environmental pollution. Moreover, the interlayer structure design reduces the processing temperature requirements, improving production efficiency and product reliability. In addition, the gap reflective film 1 uses non-metallic materials, which are environmentally friendly and avoid metal pollution. The use of the gap reflective film 1 does not affect the power generation function of the solar cell.

[0031] The beneficial effects of this application will be further illustrated below with reference to embodiments and comparative examples.

[0032] Comparative Example 1

[0033] A reflective film includes a film layer and a reflective layer stacked sequentially. The reflective layer is a PET film with 20% titanium dioxide added and has no prism structure. The film layer has a thickness of 40μm, and the reflective layer has a thickness of 80μm. Taking a 400W single-sided solar cell as an example, after testing with IV equipment (this test refers to the IEC61215 standard "Ground-mounted photovoltaic modules - design qualification and type approval", and uses the Drexel Solar-Pulse Solar Simulator (production line) to test the power of each photovoltaic module), its power generation gain is 4.589W.

[0034] Comparative Example 2

[0035] The gap reflective film consists of an adhesive film layer and a reflective film layer stacked sequentially. The adhesive film layer is made of the same material as Comparative Example 1. The reflective film layer is a resin-plated aluminum layer with a prism structure. The prism angle is 120° and the height is 12μm. It was also tested with a 400W single-sided solar cell, and the power generation gain was 7.565W.

[0036] Example 1

[0037] The gap reflective film 1 comprises a film layer 4 and a reflective film layer 2 stacked sequentially. The material and thickness of the film layer 4 are the same as in Comparative Example 1. The thickness of the reflective film layer 2 is 80 μm. Both the prism reflective layer 5 and the intermediate reflective layer 6 comprise a base material, inorganic filler, and UV additive, with mass ratios of 75:20:5 and 50:45:5, respectively. The base material is PP, the inorganic filler is titanium dioxide, and the UV additive is benzophenone. The total amount of titanium dioxide is the same as in Comparative Example 1. The reflective film layer has a prism structure with a prism angle of 120° and a height of 12 μm. The connecting layer 3 is a blend of PP base material and EMA. The thickness ratio of the prism reflective layer 5, the intermediate reflective layer 6, and the connecting layer 3 is 1:2:1. Taking a 400W single-sided solar cell as an example, the power generation gain of Example 1 was 6.986W as tested by IV equipment.

[0038] Example 2

[0039] A reflective film includes a film layer and a reflective layer stacked sequentially. The reflective layer is a PP film with 20% titanium dioxide added and has no prism structure. The film layer has a thickness of 40μm and the reflective layer has a thickness of 80μm. Taking a 400W single-sided solar cell as an example, its power generation gain is 5.162W.

[0040] Example 3

[0041] The difference between Example 3 and Example 1 is that the prism height in Example 3 is 25μm and the power generation gain is 6.883W.

[0042] The above comparison shows that the power generation gain of Example 1 (6.986W) is significantly higher than that of Comparative Example 1 (4.589W). The power generation gain is the measured power increase of the photovoltaic module with the gap reflective film 1 provided in this application attached around the solar cells and in the gaps. It directly reflects the reflectivity of the reflective structure of the gap reflective film 1. This shows that when the reflective film layer base material is PP and a prism structure is set in the reflective film layer, the light propagation path can be changed by the prism structure, and the light that originally passed through the gaps between the solar cells can be reflected back to the surface of the solar cells, effectively improving the reflection utilization rate of sunlight and thus increasing the power generation.

[0043] Meanwhile, the power generation gain of Example 1 is close to that of Comparative Example 2 (7.165W), indicating that when PP is used as the base material for the reflective film layer, the effect of increasing power generation is equivalent to that of a resin-plated aluminum layer when the reflective layer is in conjunction with the prism structure set on the reflective film layer. Moreover, PP material is more environmentally friendly, as it does not require aluminum plating and produces no pollutants.

[0044] Furthermore, the power generation gain of Example 1 is significantly higher than that of Example 2, indicating that simply using PP base material cannot significantly increase the power generation gain. Only with the cooperation of a prism structure set on the reflective film layer can its power generation enhancement effect be equivalent to that of a resin-plated aluminum layer.

[0045] The power generation gain values ​​from the test results are listed in Table 1.

[0046] Table 1

[0047]

[0048] In some embodiments of this application, the reflective film layer 2 includes a connecting layer 3, an intermediate reflective layer 6 and a prism reflective layer 5 stacked sequentially, wherein the thickness ratio of the prism reflective layer 5, the intermediate reflective layer 6 and the connecting layer 3 is 1:(1~3):(0.5~2), preferably, the thickness ratio of the prism reflective layer 5, the intermediate reflective layer 6 and the connecting layer 3 is 1:2:1.

[0049] Specifically, the reflective film layer 2 achieves a functionally graded distribution through a three-layer composite structure comprising a prism reflective layer 5, an intermediate reflective layer 6, and a connecting layer. The prism reflective layer 5, as the surface layer, ensures that the continuous phase of the base material can withstand stress deformation during hot surface micro / nano structure processing, while maintaining sufficient inorganic filler content to support the reflection efficiency of the surface prism structure. The intermediate reflective layer 6, by proportionally increasing its thickness to 1-3 times that of the prism reflective layer 5, expands the distribution space of the inorganic filler. The connecting layer 3, by proportionally increasing its thickness to 0.5-2 times that of the prism reflective layer 5, ensures effective chemical bonding with the connecting layer 3 while avoiding material waste or interfacial stress concentration due to excessive thickness, ultimately improving light utilization and structural reliability without metal coating.

[0050] The following, in conjunction with embodiments and comparative examples, will experimentally test the synergistic effect of the thicknesses of the prism reflective layer 5, the intermediate reflective layer 6, and the connecting layer 3, further illustrating that the optimal ratio of the thicknesses of the prism reflective layer 5, the intermediate reflective layer 6, and the connecting layer 3 in this application is 1:2:1. The power generation gain directly reflects the reflective efficiency of the gap reflective film 1; the peel strength reflects the interlayer bonding force, and the quantitative index of interlayer bonding strength (unit N / cm) >11 N / cm indicates that the requirements for high-reliability interlayer bonding are met; a PCT48h aging test was conducted, and yellowing was observed, which is a color change that occurs after material aging and is directly related to transmittance loss and lifespan reduction.

[0051] In Examples 4, 5, and 6, and Comparative Examples 3 and 4, the thickness of the reflective film layer 2 is 100 μm. The base material, inorganic filler, and UV additive of the prism reflective layer 5 and the intermediate reflective layer 6 are the same as in Example 1. The connecting layer 3 is the same as in Example 1, with the following specific ratios: prism reflective layer 5: base material, inorganic filler, and UV additive ratio is 75:20:5; intermediate reflective layer 6: base material, inorganic filler, and UV additive ratio is 50:45:5; and the connecting layer 3 is a blend of PP base material and EMA.

[0052] Example 4

[0053] The thickness ratio of the prism reflective layer 5, the intermediate reflective layer 6 and the connecting layer 3 in the reflective adhesive layer is 1:2:1, the power generation gain reaches 6.6W, the peel strength is 12N / cm, and there is no delamination or yellowing after PCT48h aging test.

[0054] Comparative Example 3

[0055] The thickness ratio of the prism reflective layer 5, the intermediate reflective layer 6 and the connecting layer 3 in the reflective adhesive layer is 1:0.5:0.8. The thickness of the intermediate reflective layer 6 is reduced, the power generation gain is reduced to 5.4W, the peel strength is 11N / cm, and there is no delamination or yellowing after PCT48h aging test.

[0056] Comparative Example 4

[0057] The thickness ratio of the prism reflective layer 5, the intermediate reflective layer 6 and the connecting layer 3 in the reflective adhesive layer is 1:4:2. The increased thickness of the intermediate reflective layer 6 and the adhesive layer, although the power generation gain is 6.65W, reduces the peel strength to 7N / cm and shows obvious yellowing after PCT48h aging test.

[0058] Example 5

[0059] The thickness ratio of the prism reflective layer 5, the intermediate reflective layer 6 and the connecting layer 3 in the reflective adhesive layer is 1:3:1. With the increase in the thickness of the intermediate reflective layer 6, the power generation gain is 6.65W, the peel strength is >11N / cm, and there is no delamination or yellowing after PCT48h aging test.

[0060] Example 6

[0061] The thickness ratio of the prism reflective layer 5, the intermediate reflective layer 6 and the connecting layer 3 in the reflective adhesive layer is 1:1.5:1.2. The thickness of the intermediate reflective layer 6 is reduced and the thickness of the connecting layer 3 is increased. The power generation gain is 6.56W, the peel strength is 12N / cm, and there is no delamination or yellowing after PCT48h aging test.

[0062] The above comparisons show that Comparative Example 3 differs from Example 4, demonstrating that the excessively thin reflective layer 6 in Comparative Example 3 leads to power loss; Comparative Example 4 differs from Example 4, demonstrating that the excessively thick reflective layer 6 and connecting layer 3 in Comparative Example 4 cause peeling risk; Although Example 5 has a slightly higher power output (6.65W), the excessively thick reflective layer 6 results in peel strength comparable to Example 4 (>11N / cm), without a significant improvement in long-term reliability, and instead increases material costs; In Example 6, the thickness of the reflective layer 6 is reduced, and even with an increased thickness of the connecting layer 3, the power gain compared to Example 4 is 6.56W, confirming the significant impact of the thickness of the reflective layer 6 on the power gain. Example 4 maintains a high power gain of 6.6W while also possessing peel strength >11N / cm and zero yellowing aging stability, achieving optimal synergy of technical effects, and is therefore the preferred solution of this application.

[0063] The test results for power generation gain, peel strength, and PCT48h aging test are listed in Table 2.

[0064] Table 2

[0065]

[0066] In some embodiments of this application, the prism reflective layer 5, the intermediate reflective layer 6, and the connecting layer 3 all include a base material, inorganic fillers, and UV additives. The base material is polypropylene (PP); the inorganic filler refers to particulate materials with light reflection function, specifically titanium dioxide, to improve light reflection efficiency. The UV additives refer to a combination of compounds with ultraviolet absorption function, used to absorb ultraviolet light to achieve anti-aging functions, such as, but not limited to, ultraviolet absorbers selected from one or a combination of salicylates, benzophenones, benzotriazoles, substituted acrylonitriles, and triazines.

[0067] The high proportion of the base material in the reflective film layer ensures that the material can be easily processed into prism structures using surface micro- and nano-structure techniques. This provides plasticity while maintaining the stability of the prism shape.

[0068] Compared to existing technologies, traditional PET reflective layers, due to their high melting point, cannot be directly surface-processed at subsequent production line temperatures to obtain prism structures. This necessitates the addition of an additional resin layer and aluminum plating to achieve directional light reflection. This application achieves direct molding of the prism structure within the reflective film layer 2, avoiding the process complexity associated with multi-layer composite structures. The optimized ratio of inorganic fillers to the base material ensures light reflection efficiency, while the thickness design of the interlayer structure and the multi-layer structure of the reflective film layer effectively alleviate interlayer stress concentration.

[0069] In some embodiments of this application, the base material, inorganic filler, and UV additive of the prism reflective layer 5 are mixed in a mass ratio of (60-75):(20-35):(0.1-5), and the base material, inorganic filler, and UV additive of the intermediate reflective layer 6 are mixed in a mass ratio of (45-65):(30-50):(0.1-5). Preferably, the prism reflective layer 5 is mixed in a mass ratio of 75:20:5, and the intermediate reflective layer 6 is mixed in a mass ratio of 50:45:5.

[0070] The following will, in conjunction with embodiments and comparative examples, conduct optimization tests on the mass ratio of prism reflective layer 5 and intermediate reflective layer 6 to further illustrate that the optimal ratio of this application is 75:20:5 for prism reflective layer 5 and 50:45:5 for intermediate reflective layer 6. The power generation gain is the measured power increase of the photovoltaic module with the gap reflective film provided in this application attached around the battery cells and in the gaps; it directly reflects the reflective efficiency of the reflective structure of the gap reflective film 1; the peel strength is the interlayer bonding force, and the quantitative index of interlayer bonding strength (unit N / cm) >11N / cm indicates that the requirements for high-reliability interlayer bonding are met; the PCT48h aging test simulates the same high-temperature and high-humidity harsh environment for testing the reflective adhesive layer. This simulated environment is an accelerated aging test at 85℃ and 85% relative humidity (RH). Yellowing is the color change that occurs after material aging, directly related to light transmittance loss and lifespan reduction.

[0071] In Examples 7, 8, and 9, and Comparative Examples 5, 6, 7, and 8, the thicknesses of the prism reflective layer 5, the intermediate reflective layer 6, and the connecting layer 3 are all 1:2:1. The thickness of the prism reflective layer 5 is 30 μm, and the materials and other layer thicknesses are the same as in Example 1.

[0072] Example 7

[0073] The base material, inorganic filler, and UV additive in the prism reflective layer 5 are mixed in a mass ratio of 75:20:5, and the base material, inorganic filler, and UV additive in the intermediate reflective layer 6 are mixed in a mass ratio of 50:45:5. The power generation gain is 6.6W, the peel strength is 12N / cm, and there is no yellowing after PCT48h aging test.

[0074] Example 8

[0075] The base material, inorganic filler, and UV additive in prism reflective layer 5 are mixed in a mass ratio of 60:35:5, and the base material, inorganic filler, and UV additive in intermediate reflective layer 6 are mixed in a mass ratio of 65:30:5. The power generation gain is 6.56W, the peel strength is 11N / cm, and no yellowing was observed after a 48h PCT aging test. The power generation gain is 0.56W.

[0076] Example 9

[0077] The base material, inorganic filler, and UV additive in prism reflective layer 5 are mixed in a mass ratio of 70:25:5, and the base material, inorganic filler, and UV additive in intermediate reflective layer 6 are mixed in a mass ratio of 55:40:5. The power generation gain is 6.58W, the peel strength is 11N / cm, and no yellowing occurs after a PCT 48h aging test. The power generation gain is reduced to 6.58W.

[0078] Comparative Example 5

[0079] In the prism reflective layer 5, the mass ratio of base material, inorganic filler, and UV additive is 40:59.95:0.05, and in the intermediate reflective layer 6, the mass ratio of base material, inorganic filler, and UV additive is 50:45:5. The difference between Comparative Example 5 and Example 7 is that in Comparative Example 5, the base material of the prism reflective layer 5 is reduced to 40%, the power generation gain is reduced to 5.4W, yellowing occurs after PCT 48h aging test, and the peel strength after lamination is about 8N / cm. This proves that the base material in the prism reflective layer 5 is insufficient, which affects the formation of the prism structure, reduces the sunlight reflected to the battery cell, and impairs the reflection efficiency. Insufficient UV additive reduces weather resistance, and the large proportion of inorganic filler in the prism reflective layer affects adhesion, thus resulting in poor peel strength.

[0080] Comparative Example 6

[0081] In the prism reflective layer 5, the base material, inorganic filler, and UV additive are mixed in a mass ratio of 90:9.95:0.05, and in the intermediate reflective layer 6, the base material, inorganic filler, and UV additive are mixed in a mass ratio of 50:45:5. The difference between Comparative Example 6 and Example 7 is that in Comparative Example 5, the base material accounts for 90%, the inorganic filler accounts for too little, the UV additive is reduced to 0.05%, the power generation gain is reduced to 5.3W, yellowing occurs after PCT48h aging test, and the peel strength is 11N / cm. This proves that excessive base material in the prism reflective layer 5 damages the reflection efficiency, and insufficient UV content will result in poor weather resistance.

[0082] Comparative Example 7

[0083] In the prism reflective layer 5, the base material, inorganic filler, and UV additive are mixed in a mass ratio of 75:20:5, and in the intermediate reflective layer 6, the base material, inorganic filler, and UV additive are mixed in a mass ratio of 80:15:5. The difference between Comparative Example 7 and Example 7 is that the inorganic filler in the intermediate reflective layer 6 of Comparative Example 7 is reduced to 15%, the power generation gain is reduced to 5.0W, there is no delamination or yellowing after PCT48h aging test, and the peel strength lamination result is 11N / cm, which proves that the insufficient inorganic filler in the intermediate reflective layer 6 reduces the reflection efficiency.

[0084] Comparative Example 8

[0085] In the prism reflective layer 5, the base material, inorganic filler, and UV additive are mixed in a mass ratio of 75:20:5, and in the intermediate reflective layer 6, the base material, inorganic filler, and UV additive are mixed in a mass ratio of 30:65:5. The difference between Comparative Example 8 and Example 7 is that in Comparative Example 8, the inorganic filler in the intermediate reflective layer 6 is increased to 65%, the peel strength is reduced to 6N / cm, there is no delamination or yellowing after PCT48h aging test, and the power generation gain is 6.57W, which proves that excessive inorganic filler in the intermediate reflective layer 6 damages the interlayer bonding force.

[0086] The above comparison shows that although the prism reflective layer 5 and the intermediate reflective layer 6 use the same raw materials, their different mass ratios affect the power gain, peel strength, and PCT48h test results. Examples 7, 5, and 6 demonstrate the superior technical effect of a 60-75% base material ratio in the prism reflective layer 5, while Examples 7, 7, and 8 demonstrate the superior technical effect of a 30-50% inorganic filler ratio in the intermediate reflective layer 6. Compared to direct bonding between the intermediate reflective layer and the adhesive film layer, the design of the connecting layer significantly improves the overall integrity of the gap reflective film and greatly enhances the peel strength. Therefore, Example 7 represents the optimal ratio of the prism reflective layer 5 and the intermediate reflective layer 6. The prism reflective layer 5 has the highest base material ratio, facilitating surface micro / nano structure processing to obtain the prism structure; the intermediate reflective layer 6 has a relatively high inorganic filler ratio, which, combined with the prism structure, provides higher power generation for the reflective film layer 2, while the connecting layer improves the peel strength.

[0087] The test results for power generation gain, peel strength, and PCT48h aging test are listed in Table 3.

[0088] Table 3

[0089]

[0090] In a typical embodiment of this application, a photovoltaic module is also provided, such as... Figure 3 As shown, the battery module includes a glass sheet, a battery cell, and a backsheet. Gap reflective film 1 can be provided in the gaps between the battery cells, around the perimeter, and on the solder strips. The gap reflective film 1 is bonded to the inner surface of the glass backsheet of the battery module through an adhesive film layer 4.

[0091] Specifically, the gap reflective film 1 is placed between, around, or on the solder strips of the solar cells. When light passes through the glass sheet and reaches the gap, perimeter, or solder strip, the prism structure changes the direction of light propagation before it reaches the surface of the solar cells again. The adhesive film layer 4 forms a uniform adhesive layer on the inner surface of the backsheet glass, achieving physical bonding with the backsheet through the thermal fusion properties of the material. Simultaneously, its thickness control ensures a balance between adhesive strength and module encapsulation thickness. The multi-layered structure inside the gap reflective film 1, through the synergistic effect of different proportions of base materials and inorganic fillers, achieves efficient light reflection and direction control without a metal coating, avoiding conductive interference.

[0092] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0093] The preferred embodiments of this utility model disclosed above are merely illustrative of the present utility model. These preferred embodiments do not exhaustively describe all details, nor do they limit the utility model to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of this utility model, thereby enabling those skilled in the art to better understand and utilize it. This utility model is limited only by the claims and their full scope and equivalents.

Claims

1. A gap-reflective film, characterized in that: The gap reflective film includes an adhesive film layer and a reflective film layer stacked in sequence. The reflective film layer includes a connecting layer, an intermediate reflective layer and a prism reflective layer stacked in sequence. The reflective film layer is bonded to the adhesive film layer through the connecting layer. The prism reflective layer has multiple inclined surfaces forming a convex prism.

2. The gap reflective film according to claim 1, characterized in that: The height of the convex prism is 10-25 μm.

3. The gap reflective film according to claim 1, characterized in that: The thickness ratio of the prism reflective layer, the intermediate reflective layer and the connecting layer is 1:(1~3):(0.5~2).

4. The gap reflective film according to claim 1, characterized in that: The intermediate reflective layer and prism reflective layer of the reflective film are both composed of a base material, inorganic filler and UV additive.

5. The gap reflective film according to claim 4, characterized in that: The base material is polypropylene (PP).

6. The gap reflective film according to claim 4, characterized in that: The inorganic filler is titanium dioxide.

7. The gap reflective film according to claim 1, characterized in that: The connecting layer is a blend of polypropylene base material and adhesive resin.

8. The gap reflective film according to claim 1, characterized in that: The thickness of the adhesive film layer is 30–60 μm; the thickness of the reflective film layer is 80–150 μm.

9. A photovoltaic module, characterized in that: The gap reflective film as described in any one of claims 1-8 is provided on the gaps, periphery, or solder strips of the battery cell.